2018
DOI: 10.1103/physrevb.98.024101
|View full text |Cite
|
Sign up to set email alerts
|

Local probe of irradiation-induced structural changes and orbital magnetism in Fe60Al40 thin films via an order-disorder phase transition

Abstract: Hard x-ray absorption and magnetic circular dichroism spectroscopy have been applied to study the consequential changes of the local environment around Fe atoms and their orbital polarizations in 40 nm thick Fe 60 Al 40 thin films along the order-disorder (B2 → A2) phase transition initiated by 20-keV Ne + ion irradiation with fluences of (0.75-6) ×10 14 ions cm −2. The analysis of the extended x-ray absorption fine structure spectra measured at the Fe K edge at room temperature revealed an increased number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 62 publications
3
29
1
Order By: Relevance
“…It not only offers the possibility to visualize the contributions depending on a particular backscatter but for instance, it allows also to distinguish contributions from light and heavy backscattering elements. The theoretical background of WT analysis and some cases of its application could be found elsewhere [48][49][50][51][52].…”
Section: Reverse Monte Carlo Simulationsmentioning
confidence: 99%
“…It not only offers the possibility to visualize the contributions depending on a particular backscatter but for instance, it allows also to distinguish contributions from light and heavy backscattering elements. The theoretical background of WT analysis and some cases of its application could be found elsewhere [48][49][50][51][52].…”
Section: Reverse Monte Carlo Simulationsmentioning
confidence: 99%
“…Nevertheless, the increase of the open volumes is consistent with the increased static disordering observed in the ion-irradiated films, as determined from the EXAFS measurements.DiscussionFrom the performed EXAFS measurements it is evident, that a change in the chemical composition of the nearest neighbour shell upon ion irradiation is not detected. A variation of the chemical composition can give rise to the onset of Fe-rich regions due to intermixing and would lead to changes in the relative intensity of the different features in the Fourier transform, as it is present for example in ion irradiated Fe 60 Al 40 thin films 27. This is in contrast to XRD measurements,24 where intermixing was suggested due to a decrease of the long-range order parameter S with rising ion irradiation fluence.…”
mentioning
confidence: 91%
“…A very small increase in the film thickness ($0.5 nm) due to the irradiation is revealed by the change in the oscillation frequency. The result corresponds to the $1% increase in the lattice parameter determined by X-ray diffraction (Liedke et al, 2015;Ehrler et al, 2020;La Torre et al, 2018). The peculiarities of the oscillation shapes characterize the top and bottom interfaces.…”
Section: Resultsmentioning
confidence: 81%
“…The depth and lateral distribution of the magnetized regions at the nanoscale were observed by magnetic flux lines which became apparent via the phase shift of the scattered electrons. By means of X-ray magnetic circular dichroism (XMCD) and analysis of extended X-ray absorption fine structure (EXAFS) measurements, performed on beamline ID12 at the European Synchrotron (ESRF), it was shown that an increase in the irradiation fluence provided a progressive rise in the Fe magnetic moment, revealing the occurrence of a change in the chemical disorder in the Fe 60 Al 40 alloy (La Torre et al, 2018). Recent XMCD results obtained with soft X-rays at the Helmholtz-Zentrum Berlin (HZB) have confirmed these findings (Smekhova et al, 2021).…”
Section: Introductionmentioning
confidence: 99%